Fabrication and tensile properties analysis of fibre metal laminates - See, Pei Ying. (2011)
Fibre Metal Laminates consist of several layers of metal alternated with composite materials. The initial phase of FMLs were arall, however it was only after the development of glare that FMLs became more popular in the aviation industry.